2020
DOI: 10.3390/jof6040320
|View full text |Cite
|
Sign up to set email alerts
|

Of Mice and Fungi: Coccidioides spp. Distribution Models

Abstract: The continuous increase of Coccidioidomycosis cases requires reliable detection methods of the causal agent, Coccidioides spp., in its natural environment. This has proven challenging because of our limited knowledge on the distribution of this soil-dwelling fungus. Knowing the pathogen’s geographic distribution and its relationship with the environment is crucial to identify potential areas of risk and to prevent disease outbreaks. The maximum entropy (Maxent) algorithm, Geographic Information System (GIS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…It is possible, if not likely, that C. immitis and C. posadasii may be specialized for different host reservoirs, which could vary by geographical region. One species of interest for further investigation in the southwestern US is the desert woodrat ( Neotoma lepida ), whose presence significantly overlaps with human coccidioidomycosis cases [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible, if not likely, that C. immitis and C. posadasii may be specialized for different host reservoirs, which could vary by geographical region. One species of interest for further investigation in the southwestern US is the desert woodrat ( Neotoma lepida ), whose presence significantly overlaps with human coccidioidomycosis cases [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is imperative to understanding the risk of coccidioidomycosis, especially if the geographical distribution shifts in response to climate change [ 49 ]. Soil samples positive for Coccidioides , human coccidioidomycosis case data, and important environmental drivers paired with ecological niche models have made it possible to create high-resolution estimates of the Coccidioides endemic region [ 32 , 50 , 51 ••]. Using human coccidioidomycosis data as a proxy for Coccidioides presence, Dr. Morgan Gorris and colleagues predict that by the end of the twenty-first century, warming temperatures across the dry, western US may cause the endemic region to expand north [ 51 ••].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, species distribution models (SDM), which associate occurrence records with environmental variables that are expected to affect the species probability of persistence, have been increasingly applied to soil-dwelling fungi (Hao et al 2020) and Onygenales in particular (Ocampo-Chavira et al 2020) to estimate the environmental conditions that are most suitable for this particular group of fungi. However, despite these sound advances, our knowledge remain limited to local and regional scale (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Coccidioidomycosis became nationally notifiable in 1995 (Benedict et al., 2019 ) and studies since then have confirmed and added to historical analyses by including many more atmospheric variables, geospatial techniques, and statistical modeling. This work has refined the general characterization of atmospheric controls as follows: (i) the hot and semi‐arid conditions that define the current endemic areas and potential shifts under climate change (Gorris et al., 2018 , 2019 ; Ocampo‐Chavira et al., 2020 ; Weaver et al., 2020 ); and (ii) the basic seasonality of the disease and its association with the annual lag between previous fall/winter precipitation (via soil moisture) and subsequent cases along with concurrent dry conditions (Coopersmith et al., 2017 ; Khan, 2020 ; Kolivras & Comrie, 2003 ; Park et al., 2005 ; Shriber et al., 2017 ; Stacy et al., 2012 ; Talamantes et al., 2007 ; Tamerius & Comrie, 2011 ; Weaver & Kolivras, 2018 ; Zender & Talamantes, 2006 ).…”
Section: Introductionmentioning
confidence: 99%